Kelas Edukasi Menyusui Ibu Hamil (KEMIH): Its Correlation to The Improvement of Knowledge, Self-Efficacy, and Breast Milk Production of Post-Partum Mothers - Sudirman, Jumrah; Thamrin, Halida; Marwang, Sumarni; Sabar, Syamsyuriyana; Eryanti K, Rahayu; Passe, Rosita (Window of Health : Jurnal Kesehatan, 2024)
There have been many educational programs or media used to introduce exclusive breastfeeding. However, the reality in the field shows that many people, especially mothers, still do not understand exclusive breastfeeding. Moreover, many mothers who have been educated continue to give formula milk because of misunderstandings, such as myths. For this reason, strengthening mothers’ self-efficacy needs to be carried out since it is one of the determining factors for the success of exclusive breastfeeding. Therefore, it is highly necessary to have a maternal assistance program that starts during pregnancy to strengthen the mother’s self-efficacy and continues to guide the mother after giving birth in exclusive breastfeeding. The objective of this study was to assess the effectiveness of Kelas Edukasi Menyusui Ibu Hamil (KEMIH) (English: The Breastfeeding Education Class for Pregnant Women) to increase knowledge, self-efficacy, and breast milk production of post-partum mothers. In this study, the researchers applied a quasi-experimental design. In addition, the employed approach was two groups with control. The number of samples was 61 respondents who met the pre-defined criteria (29 respondents in the intervention group and 31 respondents in the control group). The instruments in this study were modules, self-efficacy questionnaires, and electric breast pumps. The results showed that there were significant differences in the three variables, in which the obtained p-values were 0.000 (less than 0.05) for the increase in knowledge, 0.012 (less than 0.05) for the increase in mother’s self-efficacy, and 0.000 (less than 0.05) for the increase in breast milk production. This indicates that the KEMIH program is effective in increasing the knowledge, self-efficacy, and breast milk production of mothers. In addition to education programs, mothers need to have strong support from their families and health workers for the success of the breastfeeding process.